Intercultural Communication and Science and Technology Studies - Reyes-Galindo, Luis; Ribeiro Duarte, Tiago (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This timely and engaging book addresses communicative issues that arise when science and technology travel across socio-cultural boundaries. The authors discuss interactions between different scientific communities; scientists and policy-makers; science and the public; scientists and artists; and other situations where science clashes with other socio-cultural domains. The volume includes theoretical proposals of how to deal with intercultural communication related to science and technology, as well as rich case studies that illustrate the challenges and strategies deployed in these situations. Individual studies explore Europe, Latin America, and Africa, thus including diverse Global North and South contexts.
Keywords: Social sciences.; elektronické knihy; electronic books